Bisnis Dalam Peradaban Islam - Sukma Mehilda (LPPM ISNJ Bengkalis, 2019)
The most felt failure of modernization which is a direct result of the era of globalization is in the economic field. Modern capitalism which although finally able to prove its superiority from socialism, in fact, has given birth to various problems, especially for third world countries (including Muslim countries) which tend to be objects rather than subject to capitalism. Associated with the failure of Western capitalism in these Muslim countries, the realization that the roots of capitalism are not from Islam, then arouse the desire to reconstruct economic systems that are considered